Identifying and Assessing the Substance-Exposed Infant. Issue 2 (March 2015) - Clark, Lisa; Rohan, Annie
<x xml:space="preserve">Abstract</x> Abstract As the rate of opioid prescription grows, so does fetal exposure to opioids during pregnancy. With increasing fetal exposure to both prescription and nonprescription drugs, there has been a concurrent increase in identification of Neonatal Withdrawal Syndrome (NWS) and adaptation difficulties after birth. In addition, extended use of opioids, barbiturates, and benzodiazepines in neonatal intensive care has resulted in iatrogenic withdrawal syndromes. There is a lack of evidence to support the use of any one specific evaluation strategy to identify NWS. Clinicians caring for infants must use a multimethod approach to diagnosis, including interview and toxicology screening. Signs of NWS are widely variable, and reflect dysfunction in autonomic regulation, state control, and sensory and motor functioning. Several assessment tools have been developed for assessing severity of withdrawal in term neonates. These tools assist in determining need and duration of pharmacologic therapy and help in titration of these therapies. Considerable variability exists in the pharmacologic and nonpharmacologic approaches to affected babies across settings. An evidence-based protocol for identification, evaluation, and management of NWS should be in place in every nursery. This article provides an overview of identification and assessment considerations for providers who care for babies at risk for or who are experiencing alterations in state, behavior, and responses after prenatal or iatrogenic exposure to agents associated with the spectrum of withdrawal.